2021
DOI: 10.1177/10556656211026536
|View full text |Cite
|
Sign up to set email alerts
|

Care Barriers for Patients With Nonsyndromic Orofacial Clefts in Saudi Arabia: A Cross-Sectional Study

Abstract: Objective: To evaluate the barriers faced by patients with nonsyndromic orofacial clefts (NSOFC) throughout their treatment course in Saudi Arabia. Design: A cross-sectional study. Setting: Eleven different governmental health care centers across Saudi Arabia. Patients: Records of pediatric patients with NSOFC. Interventions: A questionnaire with multiple validation stages was designed to assess the barriers in care of these patients through telephonic interviews with the parents or guardians of patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
(33 reference statements)
2
3
0
Order By: Relevance
“…In this context, the parents of the ER-C group reported that the greatest care barriers were related to appointment availability, accessibility, and scheduling. This supports the findings of Allaf et al [17], who reported that, according to parents, schedule-related issues were the most common care barriers for their children. After adjusting the OR and overcoming the effects of confounding factors via the binary regression analysis, it was noted that participants in the ER-C group had primarily sought care in that location due to dental care barriers.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this context, the parents of the ER-C group reported that the greatest care barriers were related to appointment availability, accessibility, and scheduling. This supports the findings of Allaf et al [17], who reported that, according to parents, schedule-related issues were the most common care barriers for their children. After adjusting the OR and overcoming the effects of confounding factors via the binary regression analysis, it was noted that participants in the ER-C group had primarily sought care in that location due to dental care barriers.…”
Section: Discussionsupporting
confidence: 91%
“…Dental Care Barriers, which is a validated questionnaire consisting of 10 items that are designed to assess relevant factors, including geographic accessibility, schedulingrelated barriers, and appointment availability and accessibility [17]. Total scores are calculated to reflect the overall degree of barriers, ranging from 10 (no barriers) to 46 (great barriers).…”
mentioning
confidence: 99%
“…Moreover, although not significant, the AOR was increased in the northern region with a smaller population size than that of the central region, which includes the capital city and a larger population size [ 27 ]. This was also supported by a previous study conducted to assess the accessibility of medical care in children reporting more barriers for parents in rural areas than for parents in urban areas [ 28 ].…”
Section: Discussionsupporting
confidence: 71%
“…Furthermore, this study considered the different regions of Saudi Arabia, and the different regions comprised different population sizes, with the western and central regions covering the highest population frequency (more than 75% of the Saudi population) [ 27 ]. This was suggested to affect the accessibility, demand for, and burden of oral health care among the different regions [ 28 , 29 ]. In addition, the burden on parents included more difficult transportation and diverse life style in metropolitan cities compared with small cities [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation